PERLINDUNGAN HAKI DALAM NON-FUNGIBLE TOKEN DITINJAU DARI PERSPEKTIF FATWA MAJELIS ULAMA INDONESIA NOMOR: 1/MUNAS VII/MUI/5/2005 (Studi Kasus Pengguna NFT di Kota Medan) - Fahri, Fahri Laksana (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2023)
This journal examines "INTELLECTUAL PROPERTY PROTECTION IN NON-FUNGIBLE TOKENS FROM THE PERSPECTIVE OF THE INDONESIAN COUNCIL OF ULAMA FATWA NO. 1/MUNAS VII/MUI/5/2005" with a focus on the practice of NFT sales in Medan City. The research originates from the prevalent practice of buying and selling NFTs involving the plagiarism of others' works, which can harm related parties. The study aims to investigate the NFT sales practices in Medan City, analyze the factors causing NFT plagiarism, and assess the relevance of Fatwa No.1/MUNAS VII/MUI/5/2005 regarding intellectual property rights in relation to the sale of plagiarized NFT artworks in Medan City. The research employs a field research method with a descriptive approach. The results reveal that the NFT trading practice in Medan City frequently involves artworks taken from others and resold in NFT marketplaces. Factors contributing to NFT plagiarism include considerations of lower prices, the desire for profit, and a lack of decisive action from the government. Analysis of Fatwa MUI No.1/MUNAS VII/MUI/5/2005 indicates that the practice of buying and selling NFTs with plagiarism is inconsistent with the MUI's perspective on intellectual property rights. The resale of NFT artworks is considered disadvantageous and detrimental to the original creators and contradicts the principles of intellectual property protection as outlined in the MUI fatwa. Keywords: Intellectual Property Rights Protection, Non-Fungible Token